2020
DOI: 10.1039/d0sm01504k
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of polymer–colloid mixturesviafast nonequilibrium evaporation

Abstract: In drying liquid films of polymer-colloid mixtures, the stratification in which polymers are placed on top of larger colloids is studied. It is often presumed that the formation of segregated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…When dispensing a colloid-PEG droplet on a substrate at 80 °C, the resultant fast evaporation leads to a sharp increase in both the concentration of nanoparticles and PEG near the air–liquid interface. With the increasing concentration of components as well as the associated viscosity of the solution (Figure S9), a skin layer at the droplet surface forms. ,, The fast evaporation of the droplet also results in a surface capture effect. , Because of this effect, a rapidly descending air–liquid interface can kinetically capture nanoparticles near the droplet surface (Figure b). With more and more nanoparticles getting captured by the surface, nanoparticles pack into an equilateral triangular structure and then form an FCC lattice with its (111) plane oriented parallel to the droplet surface due to the attractive capillary force between nanoparticles (Figure c). ,,, To support this surface capture effect, the descending rate of the droplet air–liquid interface ( v in ) should be larger than the diffusion rate of the particles ( v p ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When dispensing a colloid-PEG droplet on a substrate at 80 °C, the resultant fast evaporation leads to a sharp increase in both the concentration of nanoparticles and PEG near the air–liquid interface. With the increasing concentration of components as well as the associated viscosity of the solution (Figure S9), a skin layer at the droplet surface forms. ,, The fast evaporation of the droplet also results in a surface capture effect. , Because of this effect, a rapidly descending air–liquid interface can kinetically capture nanoparticles near the droplet surface (Figure b). With more and more nanoparticles getting captured by the surface, nanoparticles pack into an equilateral triangular structure and then form an FCC lattice with its (111) plane oriented parallel to the droplet surface due to the attractive capillary force between nanoparticles (Figure c). ,,, To support this surface capture effect, the descending rate of the droplet air–liquid interface ( v in ) should be larger than the diffusion rate of the particles ( v p ) .…”
Section: Resultsmentioning
confidence: 99%
“…This is indicated by the blue center of the deposition, suggesting the formation of the (111) plane orientation of the FCC lattice in the skin phase. In addition, nanoparticles should be wettable by PEG (Figure e). , Otherwise, the polymer and nanoparticles would self-stratify to a polymer layer and a nanoparticle layer (Figure S11). Both the peak near 3650 cm –1 in the Fourier transform infrared spectra (FTIR) of the colloid-PEG mixture and the slightly increased diameter of colloidal nanoparticles indicate the good wettability of the PEG on nanoparticles (Figure f and Figure S12).…”
Section: Resultsmentioning
confidence: 99%
“…The study shows the stratification of the mixture may not rely on the drying rate. 35 According to the Pe = v ev H/D, the stratification of the coating is mainly related to the diffusion constant D under a constant evaporation rate. With the polymer concentration increasing under evaporation, the viscosity of the mixture near the liquid−air interface increases, .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The microstructure, or rather the distribution of nanoparticles and polymer binder in the coating, plays a vital role on the performance of SSC. The preceding works, including simulation, modeling, and experiment, show that the stratified structures of the polymer-on-top or particle-on-top can be realized by tailoring the nanoparticle/polymer interaction, hydrodynamic interactions, gyration radius or length of polymer, molecular weight of polymer, and evaporation rate, , as well as the sedimentation of aggregated particles or floating-up of lightweight particles (e.g., hollow glass spheres and aerogel particles). , Nevertheless, the implementation of these strategies puts forward high requirements for polymer-to-particle matching, processing conditions, and nanoparticle features. This demonstrates that there are still many challenges to overcome (e.g., construction and structural regulation of the hard colloidal-soft polymer composite SSC by a simple approach) before widespread industrial application of high-performance water-based composite SSC can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Processing effects are well studied for other types of binary systems where the constituents have disparate sizes, such as colloid/colloid, polymer/colloid, and linear polymer/polymer systems. These studies have shown that the ratio of the Péclet numbers of the constituents plays an important role in dictating surface enrichment in these blends. The Pe number describes the relative rates of solvent evaporation and solute diffusion: where η is the solvent viscosity, R h is the hydrodynamic radius of the particle, H is the initial film thickness, E is the rate of evaporation, k is the Boltzmann’s constant, and T is the temperature.…”
Section: Introductionmentioning
confidence: 99%